2013
DOI: 10.1177/0022002712467932
|View full text |Cite
|
Sign up to set email alerts
|

Third-Party Conflict Management and the Willingness to Make Concessions

Abstract: Third-party conflict management, particularly legal dispute resolution (arbitration and adjudication) and mediation, can help improve the willingness of disputants to make asymmetric concessions by ameliorating commitment problems and providing political cover. In both regards, and especially pertaining to commitment problems, mediation has substantial limitations when compared to legal dispute resolution. We develop these arguments and test the observable implications on the Issue Correlates of War data. To g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 103 publications
(164 reference statements)
0
15
0
Order By: Relevance
“…Why and how do disputants manage intrastate conflict? Conflict management research largely focuses on conflict characteristics and dynamics such as the balance of power, relative rebel strength, number of actors, conflict costs and the power to hurt, and the role of external parties in bringing about negotiations and mediations (Ghosn, 2010;Beardsley & Lo, 2014;Greig, 2014;Thomas, 2014;Kaplow, 2016). These conflict dynamics are frequently presented as gender-neutral.…”
Section: Conflict Managementmentioning
confidence: 99%
“…Why and how do disputants manage intrastate conflict? Conflict management research largely focuses on conflict characteristics and dynamics such as the balance of power, relative rebel strength, number of actors, conflict costs and the power to hurt, and the role of external parties in bringing about negotiations and mediations (Ghosn, 2010;Beardsley & Lo, 2014;Greig, 2014;Thomas, 2014;Kaplow, 2016). These conflict dynamics are frequently presented as gender-neutral.…”
Section: Conflict Managementmentioning
confidence: 99%
“…Research also finds evidence that domestic politics are important. Scholars argue that mediation provides political cover that enables leaders under pressure to enter mediation and accept mediated agreements (Beardsley, 2010, 2011; Beardsley and Lo, 2013; Brown and Marcum, 2011). Beardsley (2010) found that mediation is more likely for leaders with domestic audience costs , i.e.…”
Section: Mediationmentioning
confidence: 99%
“…when a leader will be punished for backing down to an enemy. Beardsley and Lo (2013) found that audience costs make asymmetric concessions more likely in mediation. Melin (2013) noted that mediation’s face-saving helped leaders accept ‘unacceptable terms in Sinai (1974), El Salvador (1988), and Mozambique (1992)’ (p. 87).…”
Section: Mediationmentioning
confidence: 99%
“…On the other hand, transparency also reduces political cover. A third party facilitating transparent negotiations will find it more difficult to claim responsibility for concessions-concessions that are even more important to domestic opposition groups than in less salient issues (Beardsley and Lo, 2014). Leaders managing contentious issues-that also hope to retain power-prefer management fora that mitigate audience costs to those that improve compliance monitoring.…”
Section: Issue Salience and Concession-making Risksmentioning
confidence: 99%